Issues of Attracting Foreign Investment in the Tourism Industry of Kazakhstan - SADUOV, Askar; MUKANOV, Beibut; MAZHITOVA, Saule; TOLEUULY, Almas; GELMANOVA, Zoya; KAZBEKOV, Turlybek (Journal of Environmental Management and Tourism, 2022)
The purpose of the study is to analyze the factors that affecting foreign flows in the tourism sector, which allows to solve several problems associated with both increasing the level of satisfaction of cultural needs of the population, and the creation of conditions for the development of forms of entrepreneurship as the main actors in the tourism industry. In this regard, the issues of attracting foreign investment in the tourism industry are in line with the use of digital platforms as the main channels of interaction with customers and transactions, as well as a means of creating investment business models for the Kazakhstan tourism industry.